Enzymatic Aerobic Alkene Cleavage Catalyzed by a Mn3+‐Dependent Proteinase A Homologue. Issue 18 (4th November 2013) - Rajagopalan, Aashrita; Schober, Markus; Emmerstorfer, Anita; Hammerer, Lucas; Migglautsch, Anna; Seisser, Birgit; Glueck, Silvia. M.; Niehaus, Frank; Eck, Juergen; Pichler, Harald; Gruber, Karl; Kroutil, Wolfgang
<x xml:space="preserve">Abstract</x> New clothes for Mn3+: Aerobic alkene cleavage of styrene‐type substrates by Trametes hirsuta is attributed to an enzyme that is dependent on manganese in oxidation state three. The enzyme has a proteinase backbone and binds Mn3+ exclusively via oxygen atoms, in contrast to all known Mn3+ enzymes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>